Customer service expectations for card merchants in South Africa. - Sadiki, Mpho (My University, 2014)
ABSTRACT Card acceptance and processing as a form factor for payment processing is a significant part of the South African retail payments landscape. For South African banks, the success of the service delivery model of card payment services to their retail merchants is of critical importance to their success and long term shareholder return on equity, this is as a result of the effect improved service levels has on long term customer loyalty and advocacy. This paper assesses what are the customer service expectations of card accepting merchants in South Africa. With the main objective being to determine using SERVQUAL model (Parasuraman, Zeithaml & Berry, 1990) what are the service attributes that are important in meeting card accepting merchant’s service expectations. A web based self-administered survey was used to gather the data findings, to which 87 merchants completed the questionnaire. The data was analysed for means test ranking using the stochastic search algorithm means test methodology (Stacey, 2006). The ranking was analysed to determine the service attributes from the respondents as ranked by order of importance, further to that significance testing (significance level: 0.05) was performed on the service attribute means to determine significance of ranking. The findings show that indeed the service attributes and expectation for card accepting merchants do differ to those of other banking services as documented in previous studies. Card accepting merchants rated the following 8 service attributes as the most important in meeting their service expectations;  The Bank performs the service right the first time  Employees of the Bank are knowledgeable and can address my questions appropriately  The Bank's employees are professional  Device uptime & communication systems  Employees of the Bank give you prompt service  The employees of my Bank understand my needs as well as that of my business  You feel safe in your as well as your customer’s transactions with the Bank  The Bank has my best interests at heart as well as that of my business The service dimension Reliability was found to be the most important service dimension as rated by the card accepting merchants. The result also found that some of the service attributes were insignificant in the delivery and meeting of merchants customer service expectations. For example service attributes like “The Bank has operating hours convenient to my business' needs and The Bank's employees provide me with personal attention as their client” were found to be insignificant Customer service expectations are not static and differ based on business segment and demographics (Sureshchandar, Rajendran & Anantharaman, 2003 and Reichfield, 2003), the findings of this research also confirm the need for banks to constantly assess the changing needs of their customers and merchants and built service models with attributes that aims to meet or exceed on the service expectations
MBA 2013
Keywords: Banks and banking -- Customer services, Consumer satisfaction, Debit and credit cards.